Fission Yeast CSL Transcription Factors: Mapping Their Target Genes and Biological Roles - Převorovský, Martin; Oravcová, Martina; Tvarůžková, Jarmila; Zach, Róbert; Folk, Petr; Půta, František; Bähler, Jürg (PloS one, 2015)
BACKGROUND: Cbf11 and Cbf12, the fission yeast CSL transcription factors, have been implicated in the regulation of cell-cycle progression, but no specific roles have been described and their target genes have been only partially mapped. METHODOLOGY/PRINCIPAL FINDINGS: Using a combination of transcriptome profiling under various conditions and genome-wide analysis of CSL-DNA interactions, we identify genes regulated directly and indirectly by CSL proteins in fission yeast. We show that the expression of stress-response genes and genes that are expressed periodically during the cell cycle is deregulated upon genetic manipulation of cbf11 and/or cbf12. Accordingly, the coordination of mitosis and cytokinesis is perturbed in cells with genetically manipulated CSL protein levels, together with other specific defects in cell-cycle progression. Cbf11 activity is nutrient-dependent and Δcbf11-associated defects are mitigated by inactivation of the protein kinase A (Pka1) and stress-activated MAP kinase (Sty1p38) pathways. Furthermore, Cbf11 directly regulates a set of lipid metabolism genes and Δcbf11 cells feature a stark decrease in the number of storage lipid droplets. CONCLUSIONS/SIGNIFICANCE: Our results provide a framework for a more detailed understanding of the role of CSL proteins in the regulation of cell-cycle progression in fission yeast.
Keywords: regulace genové exprese u hub; Gene Expression Profiling; Stress, Physiological; mitóza; cytokineze; Schizosaccharomyces pombe Proteins; Schizosaccharomyces pombe - proteiny; fyziologický stres; Transcription Factors; Mitosis; transkripční faktory; Mitogen-Activated Protein Kinases; Cyclic AMP-Dependent Protein Kinases; Schizosaccharomyces; mitogenem aktivované proteinkinasy; proteinkinasy závislé na cyklickém AMP; stanovení celkové genové exprese; Gene Expression Regulation, Fungal; Cytokinesis